2013
DOI: 10.1039/c3lc50458a
|View full text |Cite
|
Sign up to set email alerts
|

Out of the cleanroom, self-assembled magnetic artificial cilia

Abstract: Micro-sized hair-like structures, such as cilia, are abundant in nature and have various functionalities. Many efforts have been made to mimic the fluid pumping function of cilia, but most of the fabrication processes for these "artificial cilia" are tedious and expensive, hindering their practical application. In this paper a cost-effective in situ fabrication technique for artificial cilia is demonstrated. The cilia are constructed by self-assembly of micron sized magnetic beads and encapsulated with soft po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
91
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 61 publications
(93 citation statements)
references
References 26 publications
1
91
1
Order By: Relevance
“…1d), consisting of a chamber containing the artificial cilia and a side channel providing a recirculation pathway for the fluid. This differs from previous studies, where tests were always performed in a closed chamber or channel, resulting in the combination of a ciliadriven forward flow near the ciliated surface and a recirculation backflow along the opposite surface and along the periphery within the chamber or channel itself, which made the quantification of the ''net flow'' hard to achieve Vilfan et al 2010;Wang et al 2013;den Toonder et al 2008;Shields et al 2010). By reducing (not eliminating) backflow within the main cilia chamber and observing the flow profile in the recirculation pathway, our device provides a straightforward manner to characterize the ''pumping efficiency'' of our artificial cilia.…”
Section: Integrating Artificial Cilia Into Microfluidic Channelcontrasting
confidence: 42%
See 4 more Smart Citations
“…1d), consisting of a chamber containing the artificial cilia and a side channel providing a recirculation pathway for the fluid. This differs from previous studies, where tests were always performed in a closed chamber or channel, resulting in the combination of a ciliadriven forward flow near the ciliated surface and a recirculation backflow along the opposite surface and along the periphery within the chamber or channel itself, which made the quantification of the ''net flow'' hard to achieve Vilfan et al 2010;Wang et al 2013;den Toonder et al 2008;Shields et al 2010). By reducing (not eliminating) backflow within the main cilia chamber and observing the flow profile in the recirculation pathway, our device provides a straightforward manner to characterize the ''pumping efficiency'' of our artificial cilia.…”
Section: Integrating Artificial Cilia Into Microfluidic Channelcontrasting
confidence: 42%
“…The existence of a maximum value of the flow speed has also been observed in another artificial cilia system in our previous study, where an ''optimal'' actuation frequency was observed, albeit at a lower frequency (Wang et al 2013). In order to understand the reason for the existence of Change of the aspect ratio of the ellipsoidal cone at different frequencies is shown in the embedded graphs.…”
Section: Characterization Of the Fluid Flow Induced By Artificial Ciliamentioning
confidence: 99%
See 3 more Smart Citations